Scanning the human genome for signals of selection. - McVean, G; Spencer, C (2006)
The search for adaptive evolution in the human genome has reached a new era with the advent of genome-wide surveys of genetic variation. However, making sense, let alone use, of such experiments is far from straightforward. Key problems include the way in which the data have been collected, the need to control for factors such as population history and variable recombination rates, which influence the discovery rates for both true and false positives, and the inherent difficulty of falsification. Nevertheless, recent work has shown that genome scans can be used to identify both functional polymorphisms underlying selected traits and entire classes of genes enriched for signals of adaptation.